PWE-048 Dietary practices in patients with inflammatory bowel disease-food for thought. (22nd June 2015) - Aggarwal, D; Burns, H; Mclaughlin, JT; Limdi, JK
Abstract : Introduction: An epidemiological association implicating diet in IBD risk or protection is widely accepted. 1 Despite advances in aetio-pathogenesis, nutritional research has been limited by heterogeneity of study design, variability of diet, and difficulty in obtaining accurate longitudinal dietary data. Patients with IBD often make links to diet in clinical consultations, but there is a dearth of literature exploring dietary perceptions and practices in an IBD population. 2 The aim of the study was to evaluate dietary beliefs and behaviours in patients with IBD. Method: We developed a 25-item questionnaire assessing demographics, dietary beliefs and habits, impact on social life and patients' use of resources for dietary advice. The questionnaire was prospectively administered to consecutive IBD patients attending our IBD clinics from September 2013 to February 2014. Results: A total of 400 patients participated in the study. The mean age was 48.4 years; 55% were female and 88% Caucasian. Thirty-nine percent had Crohn's Disease and 51% had Ulcerative Colitis. The median disease duration was 8 years. Of the respondents, 48% felt that diet could be the initiating factor in IBD and 57% felt it could trigger a flare. Worsening of symptoms with certain food and drinks was reported by 60%, the commonest being spicy food (41%), fatty food (29%) and alcohol (21%). A minority (16%) reported improvement in symptoms with certain foods and 67% avoided certain foods to prevent relapse, with 20% never dining outside of home for fear of causing relapse. Seventy four percent of respondents believed that IBD affects appetite. On a visual analogue scale of 1–10, the difference between the mean scores outside and during relapse was 3.7 (8.0 vs. 4.3, p < 0.0001). Fifty percent of respondents had never received any formal dietary advice, and 67% requested further dietary advice. After adjusting for other predictors, the IBD subtype and ethnicity of the patients remained as significant factors for influencing beliefs held by patients. The disease subtype, gender and age of the patient were significant determinants of the impact of IBD on appetite. Conclusion: Our study showed that patients hold beliefs pertaining to the role of diet in IBD, with a high level of consistency around key perceived triggers. Whether all the symptoms reported are due to active inflammation cannot be ascertained, but the potential exists for dietary components triggering active disease and perpetuating gut injury, impacting on quality of life and health care costs. This should serve as an impetus for further patient-centred research. Disclosure of interest: None Declared. References: http://www.ncbi.nlm.nih.gov/pmc/articles/PMC3728155/ Zallot C, et al . Dietary beliefs and behavior among inflammatory bowel disease patients. Inflamm Bowel Dis . 2013 Jan;19(1):66–72